The Rise of Refinery Margins: The Case of the Energy Tax Cut in Germany - Leonard Gregor; Justus Haucap (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper evaluates the temporary reduction in energy taxes implemented by the German government between June and September 2022. We use pricing and quantity data from the wholesale market for crude oil, gasoline, and diesel and find an average pass through of 80% to 85% of the tax cut, which amounts to a 3.7 cents per liter increase in wholesale prices net of tax. We do, however, document significant treatment heterogeneity over time and across regions within Germany. When weighting price effects by quantities sold, the estimated pass-through of the tax cut decreases to about 70% for gasoline and 58% for diesel, suggesting that refinery margins increased significantly during times of higher demand.
Keywords: H22; L13; L71; Q48; 330; pass-through; tax reduction; fuel prices; wholesale markets